Aktivitas Antibakteri Ekstrak Kecombrang (Etlingera Elatior) dan Kalanduyung (Cassia Siamea) terhadap Pertumbuhan Bakteri Serta Pengaruh Rokok terhadap Kualitas Sperma Mencit Jantan - Airin Nurfaiza; Ardi Mustakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Bacterial growth is one processes carried out through binary fission for its reproduction process. Bad bacteria in their growth process must course be inhibited in several ways, one which is through the consumption several herbal or traditional plants, such as torch ginger and kalanduyung extracts. The dangers cigarette smoke can reduce the health individuals. Cigarette smoke can have an impact on reducing the number of spermatozoa caused by decrease in the diameter seminiferous tubules for 45 days. The purpose writing journal is to analyze antibacterial activity of torch ginger and kalanduyung extracts on bacterial growth and the effect of cigarettes on the quality male mouse sperm. The writing method uses qualitative type. The results and conclusions that bacterial growth can be inhibited by consuming several traditional plants such as torch ginger extract and kalanduyung leaf extract. In inhibiting growth of antibacterial activity, torch ginger extract has quite good effectiveness with concentration value 20%. The value inhibition zone formed is 17.22. The use largest concentration, namely 80%, has an effective inhibition of bacterial growth which is known to have an average inhibition zone value of 14.9 mm. Furthermore, the quality male mouse sperm does not have specific effect on the provision control treatment related to provision amount of cigarette smoke.